The potential for biochar application in “Shatangju” (Citrus reticulate cv.) orchard on acid red soil: Biochar prepared from its organic waste in an orchard - Guo, Yanjun; Qiu, Baoli; Khan, Zaid; Jiang, Hui; Ji, Qianhua; Fan, Qizhou; Khan, Muhammad Musa (Frontiers in Plant Science, 2022)
Carbonization of agricultural and forestry wastes is the focus of biochar application in agriculture. In this study, the effects of biochar on physical and chemical properties of soil and diversity in rhizosphere microorganisms, leaf nutrients and fruit quality of acid red soil in "Shatangju" orchard were studied using organic wastes from orchards. The results showed that the carbon content rate of biochar produced from organic wastes of the orchard was as high as 80%, with excellent effects on pure, pot, and orchard soil. The results suggested that the biochar produced in the orchard could meet the annual consumption of the orchard. Applying biochar can improve acid red soil's physical and chemical properties in the citrus orchard by enhancing the availability of various mineral nutrients such as nitrogen, phosphorus, potassium, calcium, magnesium and boron. The diversity in the root and rhizosphere microorganism community (fungi, bacteria, archaea) increased, and the dominant flora changed. The change range of microbial community in the field test was higher than in the pot test, especially on bacteria. The fruit quality of each treatment group with biochar was also better than that of the control group and improved fruit coloring. The 3% biochar for Citrus reticulate Blanco cv. Shatangju in the pure soil and 1.5%-3% biochar in the pot were found suitable. In the field, the biochar at the rate of 2.4 kg/plant to 3.6 kg/plant, respectively, was the best in improving soil's physical and chemical properties, foliar nutrition and fruit quality. In this experiment, the effective addition amount of biochar was different according to the planting containers and field planting densities, but the pure soil and pot planting tests can provide theoretical references for field tests and agricultural applications.